2021
DOI: 10.3390/ani11092493
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Short-Term Effects of Cold Stress on Metabolite Responses and Metabolic Pathways in Inner-Mongolia Sanhe Cattle

Abstract: Inner-Mongolia Sanhe cattle are well-adapted to low-temperature conditions, but the metabolic mechanisms underlying their climatic resilience are still unknown. Based on the 1H Nuclear Magnetic Resonance platform, 41 metabolites were identified and quantified in the serum of 10 heifers under thermal neutrality (5 °C), and subsequent exposure to hyper-cold temperature (−32 °C) for 3 h. Subsequently, 28 metabolites were pre-filtrated, and they provided better performance in multivariate analysis than that of usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…So, their time of weaning, environmental condition, and food or diet used for weaning are different. Previous studies mainly focused on the health, metabolism, and productivity of Mongolian cattle [19,24,25]. The changes in composition and structure of bacterial communities at different developmental stages of Mongolian cattle from weaning to adulthood remain untouched.…”
Section: Introductionmentioning
confidence: 99%
“…So, their time of weaning, environmental condition, and food or diet used for weaning are different. Previous studies mainly focused on the health, metabolism, and productivity of Mongolian cattle [19,24,25]. The changes in composition and structure of bacterial communities at different developmental stages of Mongolian cattle from weaning to adulthood remain untouched.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, environmental temperature may illicit an effect on the microbiota of the internal and external genitalia of bulls in various climates or during seasonal changes ( Wickware et al, 2020 ). While there is currently no direct evidence of this available in the literature, there is evidence of environmental temperatures creating both heat and cold stress in cattle that lead to changes in steroidogenesis, rumen bacterial diversity, and metabolic function ( Roth et al, 2001 ; Tajima et al, 2007 ; O'Brien et al, 2010 ; Hu et al, 2021 ). It has also been shown that certain bacteria can quickly adapt to changes in environmental temperature, altering their metabolism and cell structure as a survival mechanism ( Onyango et al, 2013 ; Alreshidi et al, 2015 ).…”
Section: Male Reproductive Tract Microbiomementioning
confidence: 99%
“…Yan et al [26] identified the Mongolian hornless allele in Chinese Sanhe cattle breeds and the 2 bp deletion in the Friesian hornless allele which is a specific marker for the hornless gene. And Hu et al [27] found 19 metabolites related to cold stress in inner Mongolian Sanhe cattle which is involved in the metabolic regulation of fat metabolism, amino acid metabolism and intestinal microbiota metabolism in response to cold in Sanhe cattle.…”
Section: Sanhe Cattlementioning
confidence: 99%